PENGARUH VOLUNTARY DISCLOSURE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP EARNINGS RESPONSE COEFFICIENT PADA PERUSAHAAN MANUFAKTUR YANG SAHAM TERDAFTAR DI INDEKS SYARIAH PADA BURSA EFEK INDONESIA - Khaddafi, Muammar (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2016)
Research to determine and analyze the effect of voluntary disclosure and corporate social responsibility influence the earnings response coefficient at manufacturing company whose shares listed on Shariah Index in Indonesia Stock Exchange. Population to be studied in this research is the entire Manufacturing Company in Indonesia Stock Exchange 2012-2014 period the shares registered in Shariah Index. Selection of the samples was determined by using purposive sampling method with the purpose to obtain a representative sample that is representative of the data to be observed in accordance with the criteria there were 30 Company. Research where the Voluntary Disclosure positive and significant impact on the companys Earning Response coeficient listed on the Jakarta Islamic Index. Corporate Social Responsibility positive and significant impact on the companys Earning Response coeficient listed on the Jakarta Islamic Index. Voluntary Disclosure and Corporate Social Responsibility positive and significant impact on the companys Earning Response coeficient listed on the Jakarta Islamic Index.